2018
DOI: 10.1021/acs.orglett.8b00382
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Functionalized Benzooxazepino[5,4-a]isoindolone Derivatives via Cesium Carbonate Catalyzed Formal [5 + 2] Annulation of 2-(2-Hydroxyphenyl)isoindoline-1,3-dione with Allenoates

Abstract: In this work, we present a strategy for the stereoselective synthesis of functionalized benzooxazepino[5,4- a]isoindolone derivatives via a CsCO-catalyzed domino β-addition and γ-aldol reaction of 2-(2-hydroxyphenyl)isoindoline-1,3-dione derivatives with allenoates, which offers an avenue for a combination of the structural unity between benzooxazepine and isoindolone motifs in synthetically useful yields with high stereoselectivities under mild conditions. Remarkably, it is the first example of highly stereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…MS (EI): m/z = 239 (M + , 52), 195 (100), 104(39), 76 (64). The spectral data match those previously reported 42. 2-(2-Hydroxy-4-methylphenyl)isoindoline-1,3-dione (2b).…”
supporting
confidence: 88%
“…MS (EI): m/z = 239 (M + , 52), 195 (100), 104(39), 76 (64). The spectral data match those previously reported 42. 2-(2-Hydroxy-4-methylphenyl)isoindoline-1,3-dione (2b).…”
supporting
confidence: 88%
“…The class of chemical compounds the title compound belongs to has members that are important intermediates for the synthesis of isoindolinone compounds and can be used to prepare fluoresce and biologically active molecules [3,4]. They can participate in the synthesis of alkaloids Aspernidine A and Aspernidine B for the preparation of anticancer drugs and antiviral drugs [5,6].…”
Section: Commentmentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33] In addition, it has been reported that allenes can react with nucleophilic compounds in the presence of carbonate catalysis (Scheme 1). [34][35][36] Shi and co-workers utilized allene esters and ketones to establish the rst synthesis of chromenes via [4 + 2] cycloaddition assisted by nitrogen-based catalysts such as DABCO and DBU (Scheme 2a). [37][38][39] In 2015, Tong and co-workers reported the synthesis of 4H-chromenes from d-acetoxy allenoates with salicylaldehyde derivatives in an amine-catalyzed reaction (Scheme 2b).…”
Section: Introductionmentioning
confidence: 99%